Size Selection of Metapenaeus dobsoni (Miers) in Stake Net Codends used in Cochin Backwaters - Thomas, Saly N.; V., Vijayan; Mathai, George; M.D., Varghese (Fishery Technology, 2025)
Stake nets constitute the most important indigenous fishing gear used for the exploitation of penaeid shrimp resources in the estuaries and backwaters of Kerala. Management and conservation measures for this fishing gear by adopting an optimum codend mesh size are proposed so as to minimize fishing mortality of juvenile shrimps. This communication deals with the selectivity experiments conducted using codends of three different mesh sizes viz. 12, 14 and 16 mm with a codend cover of 10 mm mesh size. The catch composition of 10 mm codend used by commercial fishermen was also observed for comparative analysis. Length frequency distribution of Metapenaeus dobsoni, Metapenaeus monoceros and Penaeus indicus retained in different codends and cover was calculated. Mean selection lengths (L50) of 12, 14 and 16 mm codends were 2.96, 3.95 and 4.21 cm respectively for M.dobsoni. The catch of commercial net having 10 mm codend consisted 99.3% of M. dobsoni of less than 64 mm in total length, the size at which it attains sexual maturity. Based on mean selection factor derived from the selectivity analysis, the optimum mesh size to exploit M. dobsoni of 64 mm total length was estimated as 24 mm.